1999
DOI: 10.2307/3712024
|View full text |Cite
|
Sign up to set email alerts
|

A Refuge for Some: Gender Differences in the Relationship between Religious Involvement and Depression

Abstract: Gender differences exist in religious involvement and depression, with women reporting significantly higher levels of both. Working from the position that religzous involvement is beneficial to mental health, this paper testa whether higher religious involvement directly de.creases depression and whethe.r ir acts as a buffer against the harmful effects of persistent strains in role domains for women compared to men. Resulta, based on a sample of married and divorced men and women living in Indianalx~lis, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 52 publications
4
42
0
1
Order By: Relevance
“…This could be explained by the fact that most of the participants in the present study reported being highly spiritual prior to their cancer diagnosis and most reported being involved in a faith community from the time they were children. The sample in the present study was comprised predominantly of women, which may also partially explain why spiritual support emerged as a salient theme, as the positive benefit of religious involvement on health has been consistently shown to be greater for women (Ellison & George, 1994;McCullough et al, 2000;Mirola, 1999).…”
Section: Areas Of Growth Reportedmentioning
confidence: 95%
“…This could be explained by the fact that most of the participants in the present study reported being highly spiritual prior to their cancer diagnosis and most reported being involved in a faith community from the time they were children. The sample in the present study was comprised predominantly of women, which may also partially explain why spiritual support emerged as a salient theme, as the positive benefit of religious involvement on health has been consistently shown to be greater for women (Ellison & George, 1994;McCullough et al, 2000;Mirola, 1999).…”
Section: Areas Of Growth Reportedmentioning
confidence: 95%
“…This is an important gap in the literature, because mounting evidence suggests that the roles of religious practice, support, meaning, and other important facets of religion and spirituality may be contingent on aspects of social location, culture, and circumstance. For example, several studies over the years have reported that religiousness may be more closely linked with psychological well-being (a) among women as compared with men (e.g., Idler 1987;Mirola 1999), (b) among African Americans as compared with whites (e.g., St. George and McNamara 1984;Thomas and Holmes 1992;Krause 2003), (c) among older adults as compared with younger persons (e.g., Ellison 1991), and (d) among lower SES individuals-especially those with lower levels of education-as compared with others (e.g., Pollner 1989;Ellison 1991;Krause 2006c).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies over the years have investigated the possibility that links between religiousness and mental health may vary by gender (Idler, 1987;Mirola, 1999). At first glance, this makes sense, because at virtually every age of the life course, from adolescence through late life, women tend to be more religious and more spiritual than men from otherwise comparable backgrounds.…”
Section: Gender Religiousness and Depressionmentioning
confidence: 99%